2013
DOI: 10.1016/j.neuro.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine regulation of sulfotransferase 1A1 and 2A1 expression in rat brain sections

Abstract: Sulfotransferase catalyzed sulfation regulates the biological activities of various neurotransmitters/hormones and detoxifies xenobiotics. Rat sulfotransferase rSULT1A1 catalyzes the sulfation of neurotransmitters and xenobiotic phenolic compounds. rSULT2A1 catalyzes the sulfation of hydroxysteroids and xenobiotic alcoholic compounds. In this work, Western blot and real-time RT-PCR were used to investigate the effect of methamphetamine on rSULT1A1 and rSULT2A1 protein and mRNA expression in rat cerebellum, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…One recent paper demonstrated that SULT1A3 could be induced by DA in vitro, indicating the role of SULT1A3 in CNS by protecting neuronal cells from DA toxicity [25]. Besides, our previous results showed that methamphetamine, a structural analogue of DA, could induce the expressions of rSULT2A1 remarkably in rat liver and brain [23,24]. Our recent data in vitro also revealed that the activity of SULT2A1 in HepG2 cells increased significantly after the treatment with DA, and the expression of SULT2A1 was significantly induced by specific D1 agonists (SKF-38393 and SKF 82958) that activating D1 signaling pathway selectively [26].…”
Section: Q2mentioning
confidence: 87%
See 1 more Smart Citation
“…One recent paper demonstrated that SULT1A3 could be induced by DA in vitro, indicating the role of SULT1A3 in CNS by protecting neuronal cells from DA toxicity [25]. Besides, our previous results showed that methamphetamine, a structural analogue of DA, could induce the expressions of rSULT2A1 remarkably in rat liver and brain [23,24]. Our recent data in vitro also revealed that the activity of SULT2A1 in HepG2 cells increased significantly after the treatment with DA, and the expression of SULT2A1 was significantly induced by specific D1 agonists (SKF-38393 and SKF 82958) that activating D1 signaling pathway selectively [26].…”
Section: Q2mentioning
confidence: 87%
“…Protein level of rSULT2A1 in male and female rat liver cytosol was investigated by western blot analysis [23]. In brief, 50 mg of protein from rat liver were separated in a 12% polyacrylamide gel by an electrophoresis system (Bio-Rad, Hercules, CA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In vivo, tumor-bearing mice were treated with TM208 for 18 d, and cytosol samples from the tumors were prepared as previously described [36] .…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Western blot analysis was conducted as described in a previous study [36] . Total protein (50 μg) was separated by SDS-12% w/v polyacrylamide gel electrophoresis and transferred to PVDF membranes (Pierce, Rockford, IL, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation